An alternative approach to the representation of orthotropic tensor functions in the two-dimensional case - Jemioło, S.; Telega, J.J. (Archives of Mechanics, 1996)
The aim of this paper is to derive in a simple fashion the non-polynomial representations of a class of orthotropic functions in the two-dimensional case. Scalar-valued, vector-valued, symmetric and skew-symmetric tensor-valued functions of the second order have been considered.